Comparison between dexmedetomidine and ketofol in the prevention of postoperative emergence delirium in pediatric patients undergoing orofacial cleft surgery: A randomized controlled trial - Surabhi; Poonam Kumari; Amarjeet Kumar; Chandni Sinha; Ajeet Kumar; Veena K. Singh (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Emergence delirium (ED) is a common postoperative complication in pediatric patients. To avoid postoperative ED, sedative medications have been utilized in addition to general anesthesia. In this study, the primary objective was to assess the incidence of postoperative emergence of delirium at 0-, 10-, 20-, 30-, and 60-min intervals. Secondary objective was to assess postoperative analgesia (0, 10, 20, 30, and 60 min) and hemodynamic parameters (mean arterial pressure, pulse, oxygen saturation). Material and Methods: In this randomized controlled study, 105 American Society of Anesthesiologists I and II patients, aged between 3 months and 2 years, scheduled for orofacial cleft surgery were enrolled. Patients of group I received dexmedetomidine (0.3 μg/kg), group II received ketofol (a mixture of ketamine 0.25 mg/kg and propofol 1.0 mg/kg), and group III received normal saline 10 min before extubation. The incidence of postoperative ED using the Watcha scale and the postoperative pain using the Face, Legs, Activity, Cry, Consolability (FLACC) scale were recorded. Results: The Watcha scale at the immediate postoperative period and at 10-, 20-, 30-, and 60-min intervals was 0 (1), 1 (1.75), 1 (1), 2 (2), and 3 (2) in group I, 1 (1), 2 (1), 2 (2), 2 (3), and 3 (2) in group II, and 2 (1), 3 (1), 3 (1.25), 4 (1), and 4.5 (1.5) in group III, respectively, at the above time points. On comparing group I with groups II and III, the difference was significant (P < 0.01). The FLACC score at the immediate postoperative period and at 10-, 20-, 30-, and 60-min intervals was 1 (1), 1 (1), 1 (1), 2 (2), and 3 (2) in group I, 2 (2), 2 (1), 2 (2), 2(3), and 3 (2) in group II, and 4 (1), 3 (1), 3 (1.25), 4 (1), and 4.5 (1.5) in group III, respectively, at the above time points. The FLACC score was also lower in group I in comparison to groups II and III. The difference among the groups was significant (P < 0.01). The incidence of postoperative delirium was lower in group I at 20% (7/35) than in group II at 29% (10/35) and in group III at 49% (17/35), and difference among the groups was significant (<0.01). Conclusions: We conclude that both dexmedetomidine and ketofol are effective in reducing postoperative ED. Dexmedetomidine is more effective than ketofol in preventing postoperative ED in the pediatric population.